Implementation of OHS Using the Wara Method Lifting Work of Toll Road Development Project Cisumdawu Stage III Change in Ramp Cileunyi III - Muhammad Danang Muzaki; Dewi Yustiarini (Universitas Pendidikan Indonesia, 2021)
Labor is the main capital in business development, so theymust receive work safety protection from the company. Inthe Cisumdawu Phase III Toll Road Project, the CileunyiInterchange in the vicinity of the work environment alongwith all the factors and risks can be detrimental to thehealth of workers if not managed properly. The researchmethod used in the preparation of this report is thedescriptive survey method. The result of the research thathas been carried out is that the management of K3implementation in the Cisumdawu Phase III InterchangeCileunyi Ramp III Toll Road Development Project has made apolicy in implementing occupational health safety, includingthe application of OHS support and conducting riskassessments in a job, especially in work. lifting by applyingthe WARA (Work Activities Risk Assessment) method